Efficacy and Safety of Diquafosol Ophthalmic Solution in Patients with Dry Eye Syndrome: A Japanese Phase 2 Clinical Trial - Matsumoto, Yukihiro; Ohashi, Yuichi; Watanabe, Hitoshi; Tsubota, Kazuo (Ophthalmology (Rochester, Minn.), 2012)
To investigate the dose-dependent efficacy and safety of diquafosol ophthalmic solution for the treatment of dry eye syndrome. Randomized, double-masked, multicenter, parallel-group, placebo-controlled trial. A total of 286 Japanese patients with dry eye who were prescribed topical diquafosol (1%, n = 96; 3%, n = 96) or placebo ophthalmic solution (n = 94). After a washout period of 2 weeks, qualified subjects were randomized to receive a single drop of 1% or 3% diquafosol or placebo ophthalmic solutions 6 times per day for 6 weeks. The primary outcome measure was fluorescein corneal staining score assessment. The secondary outcome measures were Rose Bengal corneal and conjunctival staining scores, tear break-up time (BUT), and subjective symptom assessment. Safety measures were clinical blood and urine examination and recording of adverse events. Fluorescein corneal staining scores significantly improved with both 1% and 3% topical diquafosol compared with placebo at 4 weeks, respectively (P = 0.037, P = 0.002). There was a dose-dependent effect among the groups. Rose Bengal corneal and conjunctival staining scores also improved significantly with both 1% and 3% diquafosol compared with placebo (P = 0.007 and P = 0.004, respectively). Subjective dry eye symptom scores significantly improved with both diquafosol ophthalmic solutions (P ≤ 0.033), although there were no significant differences in BUT compared with placebo. No significant differences between the treatment groups were observed in relation to the occurrence of adverse events. Both 1% and 3% diquafosol ophthalmic solutions are considered effective and safe for the treatment of dry eye syndrome. Proprietary or commercial disclosure may be found after the references.